2019
DOI: 10.1016/j.ijdevneu.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Application of stem cells and chitosan in the repair of spinal cord injury

Abstract: Cytology and histology obstacles have been the main barriers to multiple tissues injury repair. In search of the most promising treatment strategies for spinal cord injury (SCI), stem cell‐based transplantation coupled with various materials/technologies have been explored extensively to enhance SCI repair. Chitosan (CS) has demonstrated immense potential for widespread application in the form of scaffolds and micro‐particles for SCI repair. The current review summarizes the evidences for stem cell‐based trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…Moreover, chitosan hydrogel can also be formed to tubes, sponges, or other, quite sophisticated structures, as well as be used for co-implantation of stem cells, or controlled release of trophic factors or neuroprotective agents. 14,17,20,65,66 Since it is not possible, both from ethical, as well as experimental points of view, to test many different modifications of a biomaterial by implanting each of them in vivo, pertinent in vitro assays are needed to help narrowing down the choice to a few, promising formulations. Thus, in addition to being a bio-compatible and bio-degradable extracellular matrix replacement allowing for cell attachment and axon regrowth (such as chitosan-FPHS), the "ideal" biomaterial would contribute to regulate the balance between inflammatory events indispensable shortly after SCI, and the activity of diverse subtypes of antiinflammatory MΦ that play a major role in tissue reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, chitosan hydrogel can also be formed to tubes, sponges, or other, quite sophisticated structures, as well as be used for co-implantation of stem cells, or controlled release of trophic factors or neuroprotective agents. 14,17,20,65,66 Since it is not possible, both from ethical, as well as experimental points of view, to test many different modifications of a biomaterial by implanting each of them in vivo, pertinent in vitro assays are needed to help narrowing down the choice to a few, promising formulations. Thus, in addition to being a bio-compatible and bio-degradable extracellular matrix replacement allowing for cell attachment and axon regrowth (such as chitosan-FPHS), the "ideal" biomaterial would contribute to regulate the balance between inflammatory events indispensable shortly after SCI, and the activity of diverse subtypes of antiinflammatory MΦ that play a major role in tissue reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Prepared in various forms, such as nanoparticles, 11 electrospun fibers (in a polymer mixture with collagen and thermoplastic polyurethane 12 ), or as physical hydrogels, it has already been employed in a number of biomedical applications, for example, as wound dressing, 13 drug delivery vehicle, 14 and most interestingly, in various tissue‐engineering strategies 15‐17 . Chitosan has already been used for experimental SCI treatment, but usually as support structure for trophic factor delivery, or cell therapy 18,19 ; for review 20 . The particular chitosan formulation we used for implantation into the rat SCI site 10 was prepared from squid pen, and had a weight‐averaged molar mass (M W ) of ~550.000 g/mol, a degree of acetylation (DA) of 4% (i.e., highly deacetylated chitosan, equivalent to a deacetylation degree of 96%), a chitosan concentration (w/w) in the hydrogel (Cp) of 2.5%, and above all, was fragmented with particle sizes mainly ranging from 20 to 100 μm (i.e., about the size of cells).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further explore the treatment of NPP, we took advantage of the unique biological characteristics of NSCs. For example, NSCs can self-renew and maintain a stable number, differentiate into all tissues and cells in the nervous system, secrete more neurotrophic factors, inhibit the formation of glial scars and cavities, promote axonal regeneration, and repair injured nerves ( Itakura et al, 2017 ; Hu et al, 2019 ). However, transplantation of heterologous cells into the host can cause immune rejection and damage the transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CS exhibits in vitro neuroprotective effects on several neuronal cell lines, by exerting anti-inflammatory activities and protecting from apoptotic mechanisms [29]. More recent studies focused on the development of CS porous matrices, solutions, and hydrogels, have revealed that CS scaffolds-when implanted at the site of SCI in the sub-acute stage-provide a protective and neurotrophic microenvironment that is functional both to the survival of damaged endogenous neurons and to the differentiation of transplanted stem cells into neuronal ones [28,[30][31][32]. ALG is an anionic polysaccharide, generally extracted from brown algae (Phaeophyceae species).…”
Section: Introductionmentioning
confidence: 99%